Primary Hepatic Follicular Lymphoma Presenting as Sub-acute Liver Failure: A Case Report and Review of the Literature - Mary-Jane OU Williams; Hossein Akhondi; Omar Khan (SAGE Publishing, 2019)
Sub-acute liver failure is a term that describes the relatively sudden loss of liver function, usually >21 days and <26 weeks, with impaired synthetic function and associated encephalopathy in a person with no pre-existing liver disease or cirrhosis. It is commonly caused by viruses and drugs, less so by malignancy. Our patient is a 71-year-old Japanese man who presented with signs of sub-acute liver failure. A subsequent liver biopsy demonstrated involvement by B-cell non-Hodgkin lymphoma. Evaluation of the bone marrow demonstrated significant marrow involvement by B-cell lymphoma. The fluorescence in situ hybridization (FISH) returned positive for t(14; 18). Noted was the patient's clinical presentation of cholestasis secondary to hepatic lymphoma with no evidence of lymphadenopathy or peripheralized lymphoma. Given the disease distribution, the overall findings are consistent with primary hepatic follicular lymphoma as described in few case reports and small case series in the literature.